Activation of the Creative Economy Community in Creating Terracotta-based Local Cultural Resistance in Rural Areas - Yusmanto; Uyu Wahyudin; Ace Suryadi; Asep Saepudin (GoAcademica Research & Publishing, 2023)
The creative economy is increasingly developing in various countries, including Indonesia. It is spread throughout all corners of rural areas. The implementation of the creative economy can be driven by the presence of a community that is required to be more energetic in actualizing new ideas; thus, it affects people’s welfare. A critical issue is how the creative economy community can encourage local wisdom; hence, local culture can continue to exist in community development. This research aims to reveal the JAF community’s roles in preserving local terracotta-based culture. The research method was a field case study in the JAF Community, Jatisura Village, Jatiwangi Sub-district, Majalengka Regency. JAF’s impact as a people empowerment activator community could be in the form of (1) fostering organizational enthusiasm in the community (the growth of community movements based on the focus of its work); (2) contributing to the community’s economy (many communities were developing their business ventures); (3) creating social networks (collaboration between communities not only locally but on a national and international scale); and (4) utilizing local wisdom culture (primarily related to arts, livelihood systems, social organizations, and knowledge systems). JAF also had implications for the development of the creative economy through the exhibition subsector, which regularly displayed innovative things at various festivals.